PENINGKATAN HASIL BELAJAR MELALUI METODE COOPERATIVE LEARNING PADA MATA PELAJARAN MATEMATIKA KELAS IV SD N 2 SINAR OGAN - Ponidi, Ponidi (JURNAL MANAJEMEN PENDIDIKAN ISLAM AL-IDARAH, 2016)
Based on the fact that the low level of student learning outcomes, the authors conduct action research with a view to improve student learning outcomes. In collaboration with colleagues authors try to use cooperative learning model of learning in the learning carried out in the first cycle, the second cycle, to improve student achievement fourth grade N 2 Sinar Ogan Tanjung bintang District of South Lampung regency.Plans for improving learning through this research turned out by using the model of learning coopertive learning can improve student learning outcomes. From the evaluation results can be seen increase in the percentage of student learning outcomes that can be reached KKM with the acquisition results in prasiklus percentage of 32.15%, 42.86% the first cycle, second cycle 89.28%. Thus the author felt the need to master and use different models of learning in every learning activities in schools.